Pemberdayaan Perempuan Nelayan melalui Strategi Komunikasi Pemasaran Digital dalam Pengembangan Usaha Home Industri Krupuk Ikan Bandeng di Desa Kalanganyar, Kecamatan Sedati, Kabupaten Sidoarjo - Yuli Candrasari; Didiek Tranggono; Yushinta Aristina Sanjaya; Latif Ahmad Fauzan; Ratih Pandu Mustikasari (Syntax Idea)
Kalanganyar village, Sedati subdistrict, Sidoarjo Regency has the largest pond land in Sidoarjo (BPS, 2017). Most of the population's economy depends on business activities resulting from ponds. In an effort to increase the income of fishermen's families, among others, is the participation of fisherwomen in seeking additional income. Milkfish crackers in this village have the potential to be developed, but due to limited human resource capabilities, especially regarding knowledge in creating and developing home industry and marketing businesses, as a result the home industry of milkfish crackers in Kalanganyar village, Sedati subdistrict, Sidoarjo district cannot develop rapidly. Good. The aim of the PKM program is to provide knowledge and insight to group partners regarding making good and correct milkfish crackers with good taste, and provide insight into digital marketing management so that they can increase sales. The implementation method is carried out through training in the processing of crackers made from milkfish. In addition, training and digital marketing communication assistance were carried out at KUB Planet Bandeng. During the implementation of this activity, training was carried out regarding the processing of crackers made from milkfish as well as digital marketing communications training and assistance. The community service team also handed over appropriate technology in the form of a cracker rice cake cutting machine and a cracker dough mixing machine. Apart from that, the community service team, especially students, carried out repackaging of the milkfish cracker product and now has a new logo.